Temporomandibular joint disorders. Issue 8 (August 2020) - Collins, Timothy
The temporomandibular joint (TMJ) is prone to a number of disease states involving any one of its anatomical components. The current favoured term for problems associated with the TMJ is 'temporomandibular disorder' (TMD). TMD is one of the most common orofacial pain conditions. Patients will present to GPs and general dental practitioners as well as directly to accident and emergency, typically for referral to Oral and maxillofacial surgery, due to either significant acute pain or chronic pain that can no longer be tolerated. Common features of TMD include pain in the face and preauricular area, restricted jaw movement, and noise from the TMJs during jaw movements. TMD can coincide with poor general health, psychological co-morbidities such as depression and often affects quality of life.